A novel fatigue test method for bitumen-stone combinations under cyclic tension-compression loading - Lu Zhou; Gordon Airey; Yuqing Zhang; Weidong Huang; Chonghui Wang (Materials & Design)
Asphalt pavement distress is closely linked to the fatigue performance of asphalt mixtures. Traditional fatigue tests like the dynamic shear rheometer (DSR) cannot assess failure between bitumen and stone, while methods like the four-point bending (4PB) test are complex and require specialised equipment. This study introduces a simplified bonding fatigue (BF) test method using a universal testing machine for bitumen-stone combinations, along with three evaluation indices. Two loading modes are applied to evaluate the fatigue properties of one neat bitumen and five modified binders. The accuracy of the BF experiment is validated against the 4PB test. Results indicate that the BF experiment effectively characterises the performance degradation process and bearing capacity during the yielding stage of samples under fatigue loading. While gilsonite and high-density polypropylene significantly increase the fatigue life, they cause brittle failure without a yielding period. 18 % crumb rubber-modified bitumen and 4.5 % SBS-modified bitumen exhibit superior fatigue life with an extended yield period, making them ideal for fatigue resistance. Correlation analyses with the 4PB experiments confirm that the BF experiment accurately evaluates the bonding fatigue performance of bitumen-stone combinations. Given its simplified sample preparation and equipment needs, the BF test is a viable alternative to the 4PB test.